Cykle koniunkturalne w ubezpieczeniach - wybrane teorie - Lisowski, Jacek; Zimowski, Marcin (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Researchers have been interested in insurance cycles more or less since the mid 1970s. It was time of exceptionally strong growth in medical malpractice insurance premiums and rigorous underwriting standards in the USA. The reasons for cyclical changes in insurance are described by many theories. The most important hypotheses are: market structure fluctuations theory, theory of irrational forecasting errors, theory of measurement errors, capital constraint models, and demand side hypotheses. The authors of hypotheses mentioned above are not unanimous about the meaning of variables taken into account and their influence on underwriting cycles. The debate on sources of cyclical changes in insurance and their consequences for insurance market as well as the whole economy becomes sound especially after breaking events such as hurricanes Katrina and Andrew or terrorists attack on the WTC in New York.. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 233-241